2018
DOI: 10.1039/c7dt04733a
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, structures and efficient visible light-driven photocatalytic properties of layered cuprous halides based on two types of building units

Abstract: Three novel hybrid cuprous halides, [Me3TPT][Cu5I8] (1, Me3TPT = N,N',N''-trimethyl-2,4,6-tris(4-pyridyl)-1,3,5-triazine), [Et3TPT][Cu5I8] (2, Et3TPT = N,N',N''-triethyl-2,4,6-tris(4-pyridyl)-1,3,5-triazine), and [Me3TPT][Cu5Br8] (3), were solvothermally prepared by using in situ N-alkylated 2,4,6-tri(4-pyridyl)-1,3,5-triazine (TPT) derivatives as structure-directing agents. All the compounds feature layered structures extended by two types of building units, i.e. the chain-like Cu3I6/Cu3Br7 ({Cu3}) cluster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Thesem aterials, asw ell as the reported [(Me) 3 (4-TPT)] 2 [Cu 12 I 18 ], [63] [65] possess narrow band gaps of 1.02-2.19 eV.T he values are comparable to those of organic ammoniumso rm etal complex templated halide hybrids, [13, 15-19, 50, 71] which feature small band gaps and exhibit attractive optoelectronic properties. Therefore, we are delighted to discover that introducing N-alkylation TPT-derivatives as SDAs in halides may be an effective synthetic strategy for regulating electronic band structures,w hich can decrease the band gap and accordingly increase visible-light absorption.…”
Section: Photocatalytic Mechanismsupporting
confidence: 53%
See 3 more Smart Citations
“…Thesem aterials, asw ell as the reported [(Me) 3 (4-TPT)] 2 [Cu 12 I 18 ], [63] [65] possess narrow band gaps of 1.02-2.19 eV.T he values are comparable to those of organic ammoniumso rm etal complex templated halide hybrids, [13, 15-19, 50, 71] which feature small band gaps and exhibit attractive optoelectronic properties. Therefore, we are delighted to discover that introducing N-alkylation TPT-derivatives as SDAs in halides may be an effective synthetic strategy for regulating electronic band structures,w hich can decrease the band gap and accordingly increase visible-light absorption.…”
Section: Photocatalytic Mechanismsupporting
confidence: 53%
“…It is noteworthy that they possess smaller band gaps and show red‐ shifts with respect to the bulk β‐AgI (2.81 eV) and CuI (3.10 eV) owing to the contribution of the organic cations to conduction bands. The values are compared with those of other hybrid halides directed by conjugated organic cations, such as [MC][Ag 2 I 3 ] (2.35 eV, MC= N ‐methyl‐4‐cyanopyridinium), [(Me) 3 TPT] 2 [Cu 12 I 18 ] (1.35 eV), [Me 3 TPT][Cu 5 Br 8 ] (1.30 eV), which display the properties of semiconductor materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[42,43] Recently,o ur research focusingo nt he systematic exploration of halometallates using the conjugated polypyridine derivatives as SDAs has made some progress. [44][45][46][47] These previous study indicated that N-alkylation conjugated polypyridinec ations as SDAs ande lectron acceptors can effectively decrease the band gap and accordingly increaset he absorption of the visible light of the resultant materials. For example, the tripyridine-derivatives derived iodoargentates and iodocuprates, [Me 3 (4-TPT)][M 5 I 8 ], [Me 3 (3-TPT)][M 5 I 8 ]( M= Ag, Cu;4 -TPT = 2,4,6tris(4-pyridyl)-1,3,5-triazine,3 -TPT = 2,4,6-tris(3-pyridyl)-1,3,5-triazine), possess narrow band gaps of 1.05-2.19 eV ande xhibit excellent photodegradation activity.H ence, to further investigate the impact of different conjugated organic cations on the crystal structure and band structure on halometallates, we select the conjugated bpanth (bpanth = 9,10-bis(4-pyridyl)anthracene) as cation templates,t hrough the in situ N-alkylation synthesis, achieving a3 Di norganic-organic hybrid iodoplumbate, [Me 2 (bpanth)][Pb 4 I 10 ]( 1), which possessess mall band gap and exhibits efficient photocatalytic performance in visiblelight induced degradation.Compound 1 is synthesized by an in situ solvothermalr eaction.…”
mentioning
confidence: 94%